Maternal Nutritional Status During Pregnancy, Maternal Age At Marriage, And The Risk Of Stunting In Children Aged 24–59 Months in The Batuan Public Health Center Area, Sumenep - Irine Christiany (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Stunting is form failure growth consequence accumulation absence moderately long lasting nutrition starts from pregnancy until 24 months old , one of the problem nutritional problems suffered by toddlers that is stunting g which is condition short body or very short that occurs consequence lack nutrition and disease repetitive in long time in the fetus up to 2 years First life a child . Indicators used For identify stunting toddlers are based on Height index according to age (TB/A) according to WHO child growth standards with criteria stunting If z score TB/A < -2 Standard Deviation (SD) Period 0- 24 months is the defining period quality life so that called with period gold . This is a research analytic with approach cross sectional analysis with the chi square statistical test. The sampling technique sample that is use technique purposive sampling with amount sample of 62 respondents. Statistical test using the chi-square test with mark significant p = 0,1. Results research p value = 0.000 for variable nutritional status history Mother moment pregnant with risk the occurrence of stunting and p value = 0.000 for Maternal age with risk the occurrence of significant stunting that there is connection nutritional status history Mother moment pregnant and maternal age with risk the occurrence of stunting. Conclusion: There is connection between nutritional status Mother moment pregnant , Maternal age with risk the occurrence of stunting in toddlers age 24-59 months in The Batuan Public Health Center Area. It is expected health center more optimizing the counseling about importance married at the right age.